Smart Interaction: Sports Communication as the Key to Success in Physical Education in Elementary Schools - Zulham; Riyanto, Pulung; Wasan, Aan (Universitas Pendidikan Ganesha, 2024)
The increasing diversity of student needs and learning styles in physical education necessitates the exploration of effective sports communication techniques to enhance student engagement and learning outcomes in elementary schools. This research aims to explore and implement holistic and adaptive sports communication techniques in physical education and evaluate their impact on student engagement and achievement. A case study method was chosen to gain in-depth insights into communication practices. This study involved direct observations, semi-structured interviews with 5 physical education teachers and 30 students, as well as document analysis. The subjects of the research included physical education teachers and students, employing a qualitative thematic analysis approach to identify key patterns and themes. The findings indicate that the communication techniques applied by teachers play a crucial role in the effectiveness of learning, where traditional methods often limit interactions to one-way communication. In contrast, digital communication techniques enhance flexibility and interactivity. This research underscores the need for adaptive and inclusive communication strategies, along with teacher training, which is expected to improve the quality of physical education and create a more effective learning environment for all students.